2012
DOI: 10.1111/j.1528-1167.2012.03722.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dosage failed of first antiepileptic drug on subsequent outcome

Abstract: SUMMARYPurpose: The recent definition of drug-resistant epilepsy proposed by the International League Against Epilepsy (ILAE) stipulated failure of an adequate trial of two tolerated, appropriately chosen and used antiepileptic drug (AED) schedules to achieve seizure freedom. Doses failed were not specifically discussed. We explored the effect of the doses at which the first and second AED regimens failed on subsequent outcomes in a population of adults with newly diagnosed epilepsy followed for up to 20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 16 publications
3
20
1
3
Order By: Relevance
“…49.5 per cent; Brodie and others 2013; 47 per cent; Kwan and Brodie 2001) and 85 per cent of child patients (Yılmaz and others 2014) becoming seizure free on the first-ever AED, in comparison with only 14 per cent in this study. In human epilepsy, response to treatment is often defined as achieving seizure freedom on an unchanged treatment for 12 months (Mohanraj and Brodie 2006), a standard currently higher than that commonly used in veterinary medicine.…”
contrasting
confidence: 68%
“…49.5 per cent; Brodie and others 2013; 47 per cent; Kwan and Brodie 2001) and 85 per cent of child patients (Yılmaz and others 2014) becoming seizure free on the first-ever AED, in comparison with only 14 per cent in this study. In human epilepsy, response to treatment is often defined as achieving seizure freedom on an unchanged treatment for 12 months (Mohanraj and Brodie 2006), a standard currently higher than that commonly used in veterinary medicine.…”
contrasting
confidence: 68%
“…The type and dose of AEDs were recorded daily and standardized using a ratio, PDD/DDD, where PDD is the prescribed daily dose given and DDD the defined daily dose, a method of analysis that was previously used to assess monotherapy vs polytherapy by Lammers et al 9 and popularized in analysis of AED choice and failure by Brodie et al 10 The DDD, "the assumed average maintenance dose per day for a drug used for its main indication in adults" 11 data for each of the AEDs were obtained using the WHO Collaborating Centre for Drug Statistics Methodology. The type and dose of AEDs were recorded daily and standardized using a ratio, PDD/DDD, where PDD is the prescribed daily dose given and DDD the defined daily dose, a method of analysis that was previously used to assess monotherapy vs polytherapy by Lammers et al 9 and popularized in analysis of AED choice and failure by Brodie et al 10 The DDD, "the assumed average maintenance dose per day for a drug used for its main indication in adults" 11 data for each of the AEDs were obtained using the WHO Collaborating Centre for Drug Statistics Methodology.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, there were few objective and consistent criteria to assess whether AEDs were used adequately. Brodie's study showed that 50% DDD is an appropriate cutoff for the definition of an “adequate” trial, and failure at higher doses predicted less probability of seizure freedom . In addition, a previous study investigated the association between drug dose and long‐term response, and founded that response to AEDs may be identified at low AED doses .…”
Section: Discussionmentioning
confidence: 99%